2012
DOI: 10.4236/fns.2012.33060
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Center International Survey Related to the Nutritional Support after Hematopoietic Stem Cell Transplantation Endorsed by the ASIA Pacific Blood and Marrow Transplantation (APBMT)

Abstract: Background: The nutritional support after hematopoietic stem cell transplantation (HSCT) has not been well established due to the scarcity of clinical trials. To conduct international clinical trials in Asia, we performed the questionnaire survey to investigate the current standard of nutritional support after HSCT. Method: We sent the questionnaire to the physicians nominated by the Asia Pacific Blood and Marrow Transplantation (APBMT) members of each country/ region. Result: We received 15 responses from 7 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…Our survey is in line with similar earlier surveys that demonstrated significant variations in nutritional therapy practices in patients undergoing HSCT as well as disregard of international guidelines. These studies confirmed different nutritional practices among transplant centers in Europe [16,17] and Asia [18]. Our survey further confirmed a marked variation of nutritional practices between EBMT centers.…”
Section: Discussionsupporting
confidence: 83%
“…Our survey is in line with similar earlier surveys that demonstrated significant variations in nutritional therapy practices in patients undergoing HSCT as well as disregard of international guidelines. These studies confirmed different nutritional practices among transplant centers in Europe [16,17] and Asia [18]. Our survey further confirmed a marked variation of nutritional practices between EBMT centers.…”
Section: Discussionsupporting
confidence: 83%
“…17 Owing to weak evidence for all recommendations, there is broad variability of current clinical practice guidelines, as well as discrepancy between hospital guidelines and international recommendation. [18][19][20] Many centers also lack a standardized strategy for nutritional support in these patients. 20 Since the publication of these guidelines in 2009, important studies on the role and impact of nutritional interventions on clinical outcomes in patients undergoing HSCT have been published.…”
Section: Introductionmentioning
confidence: 99%
“…However, other elements recommended by ESPEN, i.e. body composition, physical activity and the degree of inflammation, were not routinely and uniformly monitored in both the current and previous surveys [19,20,22]. Noteworthy, although all RDs agreed that physical exercise and nutrition should be combined as one intervention to improve muscle mass, the latter was rarely assessed.…”
Section: Discussionmentioning
confidence: 95%